2018
DOI: 10.1021/acsaem.8b01864
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of Dye Layers in Dye Sensitized Solar Cells: Cooperative Adsorption of N719 and Chenodeoxycholic Acid on Titania

Abstract: The effect of the co-adsorbent chenodeoxycholic acid (CDCA) up to a concentration of 20 mM on the adsorption of the dye N719 onto titania has been investigated using neutral impact collision ion scattering spectroscopy. It is shown that the co-adsorption of CDCA changes the adsorption mode of N719 from multilayer toward monolayer. FT-IR spectroscopy shows that the adsorption of CDCA increases with increasing CDCA concentration. In contrast, the amount of N719 adsorbed onto titania shows a minimum at 10 mM CDCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…However, a recent study by Trilaksana et al shows that the effect of CDCA on the coverage of dye molecules depends on the change in concentration. 9 The coverage of dye molecules showed a trend of first decreasing and then increasing at different CDCA concentrations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a recent study by Trilaksana et al shows that the effect of CDCA on the coverage of dye molecules depends on the change in concentration. 9 The coverage of dye molecules showed a trend of first decreasing and then increasing at different CDCA concentrations.…”
Section: Introductionmentioning
confidence: 94%
“…Chenodeoxycholic acid (CDCA) is a kind of bile acid and an agent for treating diseases. 9 T h i s c o n t e n t i s Currently, the mechanism of functioning of co-adsorbents is complicated and various conclusions thereon are not uniform, such as the energy level effect of TiO 2 , the improvement of photoelectric performance, and even the change of the dye adsorption process. Studies have shown that CDCA may reduce the agglomeration of the dye and can change the multilayer dye adsorption structure into a single layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…† Furthermore, photovoltaic and incident photon-to-current efficiency (IPCE) estimations were accomplished for solar cell devices, which were prepared using platinum-coated counter electrodes and TiO 2 -covered photoanodes, which were prepared by using 0.2 mM dye solutions in 1 : 1 : 1 acetonitrile, tert-butanol and DMSO solvents; the coabsorbent chenodeoxycholic acid (CDCA, 20 mM) was used in the solution, which acts as an anti-aggregation reagent. [28][29][30][31] The dyes were absorbed on the mesoporous TiO 2 electrode. The two electrodes were sealed together aer adding redox electrolyte (Solaronix, Iodolyte HI-30) consisting of a solution of 0.6 M DMPII, 0.05 M I 2 , 0.1 M LiI and 0.5 M TBP in acetonitrile.…”
Section: Photovoltaic Performance Of Dsscsmentioning
confidence: 99%
“…Third, the co-sensitizer inhibits main-dye aggregation and thus electron recombination as well as the dark current, as a function of the coadsorbent, 22 such as chenodeoxycholic acid (CDCA). 23 Cao et al 24 presented co-sensitization of N719 with a series of pyridineanchored dyes that hindered the aggregation of the main dye N719 to benet better charge transfer, and the best PCE value achieved from the co-sensitization reached 7%, which is greater than that of the DSCs based on individual N719 (5.43%). In DSC engineering, dye aggregation needs to be avoided by the design of light-harvesting dyes with a sterical structure and the utilization of a co-sensitizer along with the main dye.…”
Section: Introductionmentioning
confidence: 99%